Aplikasi kascing pada sistem minapadi di Kelompok Sipakamase Desa Gentung Kabupaten Pangkep - Ratnawaty Fadilah; Andi Sukainah; Reski Praja Putra (DEDIKASI, 2019)
The purpose of this PKM is to provide a solution of the problems facing counterparts cultivator of milkfish and Tilapia is Sipakamase Group in Gentung Village, Labbakkang Sub District, Pangkep District. The main problems faced by fish farmers in the district are the high use of inorganic fertilizer, the more of low quantity of produce, often the attack disease and decreacing quality of ponds. The target to be achieved is to give new technology innovation on the use of vermi-compost on the cultivation of milkfish and Tilapia by applying in minapadi system. This application is expected to used as a solution of the problems facing fish farmers. The method done begins with conducting observations on ponds, plan and design of minapadi system, application of vermicompost in the pond. The result of PKM are the rise of their knowledge and skill in organic farming system that capable to reduce the cost of the production and increase pond productivity.